Prediction of Function after Shoulder Replacement - Aliyev, R. M.; Vieth, T. L.; Vieth, B. I. H.; Knobe, M. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2014)
Although shoulder arthroplasty with ensuing rehabilitation is a relatively common intervention, the factors influencing the functional outcome are still a matter of discussion. These are evaluated based on the outcome as estimated by the Constant Score and patient satisfaction. Consequently, a prediction of the outcome based on initial demographic and diagnostic parameters is shown.57 patients received an alloplastic shoulder replacement followed by short stay in-patient rehabilitation. To estimate functional results a questionnaire including the Constant Score, clinical examination, numerical rating scale for pain estimation, radiological investigation of the shoulder joint and satisfaction were recorded. A generalized linear model was fitted to evaluate the effect of covariates Constant Score at admission, discharge and the improvement in-between.47 (82%) patients were content with the treatment received. The median Constant Score at admission of 31 (±3 improved to 64 (±12) at follow-up. Patients treated by senior specialist obtained 13 (±2) points more at discharge than patients treated by less experienced surgeons. Patients with assisted physiotherapy between operation and rehabilitation achieved 8 (±2) points more. Motivated patients did 7 (±2) points. A minimal Constant Score of 40 at admission, 60 at discharge or an improvement of 30 points ensured satisfied patients.Motivated patients receiving assisted physiotherapy between operation by an experienced specialist and rehabilitation have better functional results. Age, gender, type of prosthesis and diagnosis have no effect. A Constant Score of ≥40 at admission is associated with the patients being motivated and satisfied with the treatment.
Keywords: shoulder joint; constant score; replacement; rehabilitation